A multilevel analysis of improved drinking water sources and sanitation facilities in Ethiopia: Using 2019 Ethiopia mini demographic and health survey - Azanaw, Jember; Abera, Eshetu; Malede, Asmamaw; Endalew, Mastewal (Frontiers in Public Health, 2023)
Background: Access to water, sanitation and hygiene is an important element for communicable disease control including the existing COVID-19 pandemic. This is due to water demand is growing; water availability is decrease, because of shrinking resources, increased urbanization, and pollution. This problem is higher, particularly among least developed countries like Ethiopia. This study therefore aimed at investigating on the level of improved water source and sanitation as well as their predictors in Ethiopia using EMDHS-2019. Method: Mini Ethiopian Demographic and Health Surveys 2019 database survey was used in this study. Data collection took place over a 3-month period, from March 21, 2019, to June 28, 2019. A total of 9,150 households were selected for the sample, of which 8,794 were engaged. Among involved households, 8,663 were successfully interviewed at response rate of 99%.The dependent variables measured in this study were improved drinking water sources and sanitation facilities. Due to the nested nature of DHS data, multilevel binary logistic regression analysis was done using Stata-16. Results: Majority (72.62%) of household heads were males and 69.47% of participants were from rural area. The highest proportion (47.65%) of educational status was no education while the lowest (9.89%) was higher education. About 71.74 % (95% CI= (70.78%-72.68%) and 27.45 % (95% CI= (26.52%-28.40%)) of the households have accessed improved water source and sanitation, respectively. Based on the final model results, wealth index, educational status, and having television in individual level variables while community level poverty, community level education, community level media exposure, and place of residence were statistically significant predictors of getting improved water source and sanitation. Conclusion: Generally, the level of accessing improved water sources is moderate but it lack the progress. While accessing improved, sanitation was lower. Wealth index, educational status, and having television, community level poverty, community level education, community level media exposure and place of residence were statistically significant predictors of getting improved water source and sanitation. Based on these findings, great improvements should be made in providing access to improved water source and sanitation facilities in Ethiopia.